2013
DOI: 10.1039/c3ta11226h
|View full text |Cite
|
Sign up to set email alerts
|

Bicrystalline TiO2 with controllable anatase–brookite phase content for enhanced CO2 photoreduction to fuels

Abstract: Among the three naturally existing phases of TiO 2 , brookite is the least studied as a photocatalyst. In this study, single-phase anatase and brookite, and mixed-phase anatase-brookite TiO 2 nanomaterials were synthesized through a hydrothermal method. The anatase-brookite phase content was controlled by adjusting the concentration of urea in the precursor solution. XRD, Raman spectroscopy, and highresolution TEM were used to confirm the crystal structures. SEM and TEM analyses demonstrated that anatase TiO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(154 citation statements)
references
References 51 publications
8
143
0
3
Order By: Relevance
“…Moreover, the presence of brookite in the mixture can reduce the recombination of hole-electron pairs. The band gap was also widened with increasing brookite content [34]. This is why NA-165 (3.03 eV, 6% brookite content) and NA-185 (3.05 eV, 10% brookite content) exhibited similar MO photocatalytic degradation activity.…”
Section: Photocatalytic Activitysupporting
confidence: 48%
“…Moreover, the presence of brookite in the mixture can reduce the recombination of hole-electron pairs. The band gap was also widened with increasing brookite content [34]. This is why NA-165 (3.03 eV, 6% brookite content) and NA-185 (3.05 eV, 10% brookite content) exhibited similar MO photocatalytic degradation activity.…”
Section: Photocatalytic Activitysupporting
confidence: 48%
“…Adapting the procedure reported by Zhao et al [45], some of us showed that pure brookite, anatase and rutile with a well-defined shape and dimension can be obtained using titanium (IV) bis(ammonium lactate) dihydroxide, Ti(NH 4 C 3 H 4 O 3 ) 2 (OH) 2 , and varying the concentration of urea in aqueous solution (0 to 7.0 M) at 160 • C for 24 h (Figure 2). Pure brookite nanorod formation was favored by higher urea concentrations, corresponding to higher pH values due to urea decomposition, in accordance with the literature [45,46].…”
Section: Synthesismentioning
confidence: 99%
“…Thermodynamically, rutile is the most stable phase while both anatase and brookite are metastable, transferring to rutile under heat treatment, typically at temperature ranging between 600 and 700°C [2]. Among the TiO 2 crystalline forms, anatase and rutile are the most widely investigated polymorphs, with anatase generally found to be more photocatalytically active than brookite and rutile, but some reports illustrate the synergistic effect found in the composite mixture of anatase-brookite and anatase-rutile to be responsible for the enhanced photocatalytic activity [3,4]. However, because of the large band gap, anatase (3.20 eV) begins to absorb UV light around 388.5 nm, and brookite (3.14 eV) absorbs at around 395 nm, whereas the absorption onset of rutile (3.02 eV) occurs around 411 nm [5].…”
Section: Introductionmentioning
confidence: 99%